Finite element modeling of wire drawing process - Ang, Boliang (2009)
In this final year project (FYP), single stage and multi stages wire drawing simulation were carried out using the ABAQUS Finite Element (FE) software. The process variables such as Reduction area (RA), die angle (α) and coefficient of friction (μ) between the die and the wire vary in both single and multi stages simulation. Manipulating the three different process variables, the optimum result for the wire drawing process can be determined and identified. Residual stresses in the direction of axial, radial and circumferential are discussed and analysis in this FYP. These three residual stresses are taken at the transverse cross sectional area of the wire (center to the surface edge) and the multi stages shows a reduction in the tensile residual axial stress at the outer edge of the wire compare to single stage. The trends of these three stresses are discussed and compared with literature values to verify the simulation. No experimental work was under taken. Result of the hydrostatic stress that occurs at the center of the wire was obtained to determine the effect of friction. The coefficient of friction values did not affect the hydrostatic stress at the center of the wire. The FE results of the wire drawing load were compared with the closed form solution of the Slab Method (SM). Reaction force obtained from the ABAQUS FEM software is used to determine the residual stress experienced by the wire. Comparing the SM and FEM is to verify that the simulation of the wire drawing is realistic and FEM shows a more accurate result.